PELATIHAN PENGETAHUAN DASAR DALAM PENGELOLAAN HOMESTAY DI DESA WISATA TANJUNGJAYA KABUPATEN PANDEGLANG - Yudhiet Fajar Dewantara; Imam Ardiansyah; Antonius Rizki Krisnadi; Dewanta Facrureza; Prayogo Susanto (Politeknik Negeri Sriwijaya, 2023)
Increasing benefits is the main goal of rural community empowerment initiatives. Therefore, its role and existence is very important in helping to encourage self-sufficiency and improve the rural economy. Tanjung Lesung is a popular tourist spot in Indonesia whose strategic location is very important in the development of a tourist village. However, the public's perception of the development and planning of tourism villages is not yet optimal. The low level of public awareness in improving the quality of tourism villages and homestays in the regions is one example of the need for assistance from academics. This program is intended to provide basic training in homestay management. The method used in this service is to conduct presentations and discussions, regarding understanding of tourist villages, homestay management, sapta pesona and traditional food production through a process of mentoring and monitoring. The subject of the activity was 34 people who became homestay owners who were members of the Tanjung Jaya Village Tourism Awareness Group (Pokdarwis). The conclusion from this community service activity is that good homestay management is a key factor in creating a safe, comfortable and tourist-friendly tourist village. This is what tourists expect so that in managing homestays, they must meet service product standards so that the village community's economy can increase